Fast Food Consumption, Physical Activity, and Knowledge of Diabetes in Relation to Body Mass Index in Urban Adolescents: A Cross-Sectional Study - Indah Puspitasari; Amzal Mortin Andas; Ashar Prima; Maratun Shoaliha; Andi Tenri Nurwahidah (Direktorat Politeknik Kesehatan Makassar, 2026)
Urban adolescents tend to increase fast-food consumption and engage in unbalanced physical activity, which may contribute to abnormal Body Mass Index (BMI) and increase the risk of type 2 diabetes mellitus (DM). This study aimed to analyse the relationships among diabetes mellitus knowledge, fast-food dietary patterns, and physical activity with BMI among adolescents. A cross-sectional study was conducted among 290 urban adolescents from public senior high schools in Bekasi City, Indonesia, in December 2025, using stratified cluster sampling. DM knowledge was measured using the Diabetes Knowledge Questionnaire-24 (DKQ-24), fast-food intake using the Food Frequency Questionnaire (FFQ), and physical activity using the International Physical Activity Questionnaire (IPAQ). BMI was calculated from weight and height measurements. Data were analysed using Chi-Square and binary logistic regression tests with a significance level of α = 0.05. Fast-food dietary pattern (χ2 = 11.237; p = 0.010) and physical activity (χ2 = 17.584; p = 0.001) were significantly related to BMI; DM knowledge was not (χ2 = 1.838; p = 0.934). Fast-food dietary pattern was the dominant clinical factor for abnormal BMI (OR = 2.447; 95% CI 0.852–7.032; p = 0.098). Although fast-food dietary patterns showed a higher odds ratio for abnormal BMI, the association was not statistically significant (p = 0.098); however, the finding may still indicate a potential clinical trend that warrants attention. Physical activity was significantly associated with adolescent BMI. Nurses and health professionals should develop school-based nutrition education to reduce fast-food consumption and prevent early type 2 DM.